Nanopatterning with interferometric lithography using a compact λ = 46.9-nm laser - Rocca, Jorge J., author; Menoni, Carmen S., author; Parkinson, Bruce Alan, author; Lu, Yunfeng, author; Pietrasanta, L., author; Ludueña, S., author; Marconi, Mario Carlos, author; Grisham, Michael Eric, author; Vaschenko, Georgiy O., author; Capeluto, Maria G., author; IEEE, publisher (Colorado State University. Libraries, 2006)
We report the imprinting of nanometer-scale gratings by interferometric lithography at λ = 46.9 nm using an Ne-like Ar capillary discharge laser. Gratings with periods as small as 55 nm were imprinted on poly-methyl methacrylate using a Lloyd's mirror interferometer. This first demonstration of nanopatterning using an extreme ultraviolet (EUV) laser illustrates the potential of compact EUV lasers in nanotechnology applications.
Keywords: nanotechnology; photolithography; x-ray lasers; x-ray lithography